Amino acid availability and energy value of acorn in the Iberian pig - Aguilera, J F; Nieto, R; Rivera, M; García, M A (Livestock Production Science, 2002)
Two experiments have been performed to determine amino acid digestibility and energy value of acorn (Quercus rotundifolia L.) for Iberian pigs. In experiment 1 ileal digestibility of amino acids was determined in ﬁve ileum-cannulated growing pigs fed whole ground acorn. An estimation of endogenous protein losses was carried out by feeding a protein-free diet, added (180 g/kg) or not with acorn hulls. True ileal digestibility of all essential amino acids measured was high (0.798–1.03) except for arginine (0.523), lysine (0.601), isoleucine (0.760), leucine (0.777) and phenylalanine (0.716). The average value for the digestibility of the sum of amino acids was 0.664. Lysine was the ﬁrst limiting amino acid compared with the amino acid proﬁle of the ideal protein for pigs. In experiment 2, total tract digestibility of nutrients and N balance were determined in ﬁve, non-cannulated pigs offered whole acorns. High coefﬁcients for the apparent total tract digestibility of dry matter (ApDM) (0.830) and energy metabolizability (ME/GE; 0.805) were found. ME content for acorn kernel was 16.6 MJ/kg DM, while the apparent total tract digestibility of total N (ApTN) was as low as 0.408. However, a positive N retention was observed (3.7 g/day). Comparing experiments 1 vs. 2, inclusion of acorn hulls resulted in a marked decrease in DM intake, ApTN and in N retention (25.1 g/day, in total tract data from experiment 1). The negative effects of acorn hulls on protein digestibility and N balance were corroborated in rats given similar amounts of either whole ground acorn or ground acorn kernel. Dietary supplementation with lysine is proposed to achieve a higher efﬁciency of protein accretion in the Iberian pig when fed on acorn.
Keywords: acorn; amino acids; energy value; pig-feeding and nutrition; protein quality

Amino acid availability and energy value of acorn in the Iberian pig - Aguilera, J. F.; Nieto, R.; Rivera, M.; Garcıa, M. A. (Livestock Production Science, 2002)
Two experiments have been performed to determine amino acid digestibility and energy value of acorn (Quercus rotundifolia L.) for Iberian pigs. In experiment 1 ileal digestibility of amino acids was determined in ﬁve ileum-cannulated growing pigs fed whole ground acorn. An estimation of endogenous protein losses was carried out by feeding a protein-free diet, added (180 g/kg) or not with acorn hulls. True ileal digestibility of all essential amino acids measured was high (0.798–1.03) except for arginine (0.523), lysine (0.601), isoleucine (0.760), leucine (0.777) and phenylalanine (0.716). The average value for the digestibility of the sum of amino acids was 0.664. Lysine was the ﬁrst limiting amino acid compared with the amino acid proﬁle of the ideal protein for pigs. In experiment 2, total tract digestibility of nutrients and N balance were determined in ﬁve, non-cannulated pigs offered whole acorns. High coefﬁcients for the apparent total tract digestibility of dry matter (ApDM) (0.830) and energy metabolizability (ME/GE; 0.805) were found. ME content for acorn kernel was 16.6 MJ/kg DM, while the apparent total tract digestibility of total N (ApTN) was as low as 0.408. However, a positive N retention was observed (3.7 g/day). Comparing experiments 1 vs. 2, inclusion of acorn hulls resulted in a marked decrease in DM intake, ApTN and in N retention (25.1 g/day, in total tract data from experiment 1). The negative effects of acorn hulls on protein digestibility and N balance were corroborated in rats given similar amounts of either whole ground acorn or ground acorn kernel. Dietary supplementation with lysine is proposed to achieve a higher efﬁciency of protein accretion in the Iberian pig when fed on acorn.
Keywords: acorn; amino acids; energy value; pig-feeding and nutrition; protein quality